Economic analysis of integrated vegetable-poultry production systems in the Babati District of Tanzania - Habiyaremye, Naphtal; Ochieng, J.; Heckelei, T. (Springer, 2021)
Integrated vegetable–poultry production system has recently attracted attention both from the scientific and policy making communities for its potential contribution to food security as well as the opportunities it offers in improving the livelihoods of smallholder farmers in Tanzania. Despite the efforts made, its benefits and costs in heterogeneous and real-world settings are not fully understood. Despite the promising design of the vegetable–poultry production system, rather little is known of its profitability and its contribution to better living conditions of rural households in different real-world settings. The same applies regarding the knowledge on factors influencing the decision to adopt such an integrated system.Using cross-sectional data collected from 250 households in Babati district of Tanzania, we employ a gross margin analysis and a logit model to evaluate the profitability and to investigate the factors influencing the decision to integrate vegetable and poultry production systems.We find that the integrated vegetable–poultry production system is more profitable than vegetable farming alone and the profitability increases as the poultry flock size increases. An integrating household should keep 18 birds to get significant higher profit than non-integrator. Furthermore, gender and education level of the household head, awareness of integration benefits, land owned, household size, off-farm income, and total income received by the household influence the decision to integrate vegetable and poultry.The study strongly promotes the integration of vegetable–poultry production system and highlights the influence of gender and awareness of integration benefits on the decision to integrate vegetable and poultry. Hence, the policy implication is to empower women and provide capacity building through training and extension services such as provision of affordable and improved vegetable seeds and poultry breeds.